The HEADS-ED: Evaluating the Clinical Use of a Brief, Action-Oriented, Pediatric Mental Health Screening Tool. Issue 1 (January 2020) - Cappelli, Mario; Zemek, Roger; Polihronis, Christine; Thibedeau, Nathalie R.; Kennedy, Allison; Gray, Clare; Jabbour, Mona; Reid, Sarah; Cloutier, Paula
Abstract : Objectives: This effectiveness study aimed to evaluate the clinical use of the HEADS-ED tool for patients presenting to a pediatric emergency department (PED) for mental health (MH) care. Methods: In this pragmatic trial, PED physicians used the HEADS-ED to guide their assessment and identify areas of MH need in 639 patients (mean [SD], 15.16 [1.40] years; female, 72.6%) who presented to the emergency department with MH concerns between May 2013 and March 2014. Results: The HEADS-ED guided consultation to psychiatry/crisis, with 86% receiving a recommended consult. Those with a HEADS-ED score of greater than or equal to 8 and suicidality of 2 (relative risk, 2.64; confidence interval, 2.28–3.06) had a 164% increased risk of physicians requesting a consult compared with those with a score of less than 8 or greater than or equal to 8 with no suicidality of 2. The HEADS-ED mean score was significantly higher for those who received a consult (M = 6.91) than those who did not (M = 4.70; P = 0.000). Similarly, the mean score for those admitted was significantly higher (M = 7.21) than those discharged (M = 5.28; P = 0.000). Agreement on needs requiring action between PED physicians and crisis intervention workers was obtained for a subset of 140 patients and ranged from 62% to 93%. Conclusions: Results support the HEADS-ED's use by PED physicians to help guide the assessment and referral process and for discussing the clinical needs of patients among health care providers using a common action-oriented language.